Maladaptation diseases as disorders of intraorganismal individuation - Lissek, Thomas (Biosystems, 2025)
The present work introduces the hypothesis that various human maladaptation diseases including addiction, cancer, autoimmunity, fibrosis, depression, chronic pain and post-traumatic stress disorder share a universal functional pattern in that they are caused by defects in goal state integration of physiological subsystems into whole-organism goal states and by the resulting emergence of new levels of individuality within the organism. In this framework, a general mechanism in ontogenetic maladaptation is the intraorganismal individuation of subsystems via physiological adaptation mechanisms, which results in these systems becoming uncoupled from the rest of the organism and developing disproportional autonomy at the cost of whole organism health. A central mechanism for mediating continued dysfunction in these disorders is the formation and maintenance of maladaptive memories. A potential universal therapeutic principle for maladaptation disorders is to provide physiological integration pressure to force subsystems to integrate back into the functional organization of the whole organism.